Announcements of Interest Rate Forecasts: Do Policymakers Stick to Them? - Nikola Mirkov; Gisle James Natvik (Norges Bank, 2013)
If central banks value the ex-post accuracy of their forecasts, previously announced interest rate paths might affect the current policy rate. We explore whether this "forecast adherence" has influenced the monetary policies of the Reserve Bank of New Zealand and the Norges Bank, the two central banks with the longest history of publishing interest rate paths. We derive and estimate a policy rule for a central bank that is reluctant to deviate from its forecasts. The rule can nest a variety of interest rate rules. We find that policymakers appear to be constrained by their most recently announced forecasts.
hdl:11250/2496698
Keywords: E43; E52; E58; 330; Taylor rule; interest rates; forecasts; adherence